(untitled) - 1953-; Nealon, Kevin; 1962-; Garlin, Jeff (Columbia TriStar Home Entertainment, 2003)
When two fathers find themselves out of work, they decide to start a day care center. When their business starts to take off, the head of a competing prestigious childrens academy tries, with hilarious results, to put them out of business.
Keywords: Drama; Father and child; Drama; Day care centers; Comedy films; Films for the hearing impaired; Feature films